State Responses to Nuclear Proliferation - Chappell, Brian K. author. (orcid)0009-0002-2804-3638 Link aut Link
XLVIII, 412 p. 17 illus., 14 illus. in color.
Keywords: Contemporary fears of rogue state nuclear proliferation and nuclear terrorism pose unique challenges for the global community. This book offers a unique approach by examining why states that have the military capability to severely damage a proliferating state’s nuclear program instead choose to pursue coercive diplomacy. The author argues cognitive psychological influences, including the trauma derived from national tragedies like the September 11th attacks and the Holocaust, and a history of armed conflict increase the threat perceptions of foreign policy decision-makers when confronting a state perceived to be challenging the existing power structure by pursuing a nuclear weapon. The powerful state’s degree of perceived threat, combined with its national security policies, military power projection capabilities, and public support then influence whether it will take no action, use coercive diplomacy/sanctions, or employ military force to address the weaker state’s nuclear ambitions. Brian K. Chappell, PhD served twenty-eight years in the United States Air Force and is a veteran of the Afghanistan War. He is a career Nuclear and Missile Operations Officer and has served as a Middle East policy senior advisor to the Under Secretary of the Air Force for International Affairs, the Chairman of the Joint Chiefs of Staff, and the Under Secretary of Defense for Policy.